THE INFLUENCE OF AUDIT REPORT LAG, AUDIT REPUTATION, AND AUDIT TENURE ON THE ACCEPTANCE OF GOING CONCERN AUDIT OPINIONS - Ahmad Syauqi; Sairin Sairin; Lia Sahara; Rananda Septanta (Universitas Dharmawangsa Medan, 2026)
This study aims to obtain empirical evidence regarding the influence of audit report lag, audit reputation, and audit tenure on the acceptance of going concern audit opinion. This study was conducted by analyzing the financial statements of companies in the Consumer noncyclical sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 research year. The sample used in this study were Consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 period using a purposive sampling technique with predetermined criteria of 125 companies and obtained 39 companies. The number of samples was 39 companies listed on the Indonesia Stock Exchange (IDX) in 20192024 samples with a period of 5 consecutive years and produced 195 data. The data used in this study are secondary data in the form of financial statements from each company that has been used as a research sample. The variables used in this study are the audit report lag variable as the first variable, audit reputation as the second independent variable, and audit tenure as the third variable. The analysis technique used was logistic regression analysis with the help of E-Views 12. The results of this study indicate that audit report lag, audit reputation, and audit tenure simultaneously influence the acceptance of a going-concern audit opinion. However, partially, audit report lag and audit reputation do not have a significant effect. Audit tenure, on the other hand, significantly influences the acceptance of a going-concern audit opinion. Keywords: Going-Concern Audit Opinion, Audit Report Lag, Audit Reputation, Audit Tenure